Effect of electron beam radiation on the properties of natural rubber/multiwall carbon nanotube nanocomposites - Mohammad Khalid (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Natural rubber (NR) is soft and sticky with very low mechanical and thermal properties, making NR incompetent for industrial use. Vulcanization of NR increases the crosslinking density and thereby improves the physical and mechanical properties of rubber. However, conventional vulcanization using sulphur possesses several disadvantages in terms of the processing and environmental concerns. Moreover, large quantity of filler loading is required in order to enhance the vulcanized rubber properties. Nanofillers, such as carbon nanotubes (CNTs) are one of the most exciting discoveries in nanoscale sciences. The interest in CNTs is increasing due to their unique properties, large surface area and wide range of application in biomedical and engineering aspects. In this study the effect of CNTs on the properties of standard Malaysian rubber (SMR) was investigated before and after the SMR/CNTs nanocomposites were subjected to vulcanization. The SMR/CNTs nanocomposites at CNTs concentration ranging from 1-10 parts per hundred of rubber (phr) were prepared via solvent casting method. Toluene was used as a solvent for both dispersing the CNTs and dissolving the natural rubber. The nanocomposites were crosslinked by using sulphur vulcanization and electron beam (EB) radiation. The EB radiation was carried out by using a 3.0 MeV electron beam machine at doses ranging from 0 to 200 kGy in air and room temperature. Trimethylolpropane triacrylate (TMPTA) was used as accelerator to enhance the crosslinking during radiation process. The effects of CNTs loading, sulphur vulcanization and EB radiation on the mechanical, thermal, dynamic and morphological properties of SMR/CNTs nanocomposites were investigated. Wide-angle X-ray scattering (XRD), high resolution transmission electron microscopy (HRTEM) and field emission scanning electron microscopy (FESEM) were also employed to characterize the morphology and CNTs dispersion of the nanocomposites. It was found that the increasing CNTs loading in SMR caused an enhancement in the tensile strength (Ts), modulus at 100% (M100), thermal stability and storage modulus of SMR with a concomitant decline in elongation at break. A further increase in the Ts, M100, thermal stability and gel fraction was observed upon crosslinking of SMR/CNTs nanocomposites by using sulphur vulcanization system and electron beam (EB) radiation. Detailed studies involving radiation was carried out at 4 phr CNTs loading which was found to show optimum Ts after sulphur vulcanization of the SMR/CNTs nanocomposites. TMPTA was found to be efficient in acceleration of the EB radiation induced crosslinking of the nanocomposites. The XRD studies showed the intercalation of CNTs has taken place in SMR matrix and the CNTs can effectively act as nucleating agent. Studies on HRTEM revealed that the electron beam irradiation of SMR/CNTs nanocomposites upto 150 kGy improves dispersion of CNTs in SMR matrix. The addition of TMPTA was found to cause further improvement the dispersion of CNTs when the SMR/CNTs nanocomposites were exposed to radiation. However it was evident from this work that at above 150 kGy, the radiation damage of CNTs and radiation induced degradation of SMR has occurred. Additionally, it is also apparent from HRTEM micrograph that at 7 phr CNTs loading agglomeration of CNTs had occurred, which caused the overall properties of SMR/CNTs nanocomposites to drop.